2018
DOI: 10.21475/ajcs.18.12.05.pne821
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and stability of grain yield in soybean

Abstract: The aim of this work was to analyze the adaptability and stability of soybean grain yield in fifteen environments in Paraná through different methodologies. Trials were conducted to test the genotypes SYN 1049; SYN 1152; SYN 1059; SYN 3358; SYN 1163; and, SYN 1157, at five sites with three different sowing times in 2011/2012 season. The analyzed character was grain yield per hectare. The analysis of adaptability and stability was performed by bissegmented regression, factors analysis and AMMI analysis. The est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
5
6
0
Order By: Relevance
“…The genotypes namely MP3288, BRW 3775 and DBW110 were found to be better adaptable genotypes based on PRVG and PRVG*GM whereas UAS462, UAS385 recorded low adaptability under restricted irrigated timely sown conditions across major locations of wheat producing zone of the country. Similar results was already reported by Silveira et al,( 2018). Grain yield of wheat genotypes differed to large extent as per BLUP and BLUE values across zone for studied conditions (Fig 1).…”
Section: Resultssupporting
confidence: 89%
“…The genotypes namely MP3288, BRW 3775 and DBW110 were found to be better adaptable genotypes based on PRVG and PRVG*GM whereas UAS462, UAS385 recorded low adaptability under restricted irrigated timely sown conditions across major locations of wheat producing zone of the country. Similar results was already reported by Silveira et al,( 2018). Grain yield of wheat genotypes differed to large extent as per BLUP and BLUE values across zone for studied conditions (Fig 1).…”
Section: Resultssupporting
confidence: 89%
“…The genotype x environment interaction represents the differential phenotypic response of genotypes grown under different environmental conditions that cannot be explained by genotypic or environmental components (Cruz et al 2012). The results obtained by Silveira et al (2018), studying the effects of adaptability and stability on grain yield in soybean, corroborate with the results obtained from this study, confirming that there are genotypes adapted to specific environments and possibly genotypes with generalist adaptation, which is the premise of the genotype x environment interaction. Previous studies in the southern region of Minas Gerais, Brazil, also reported the existence of genotype x environment interactions in the soybean crop (Gesteira et al 2015, Silva et al 2016, Silva et al 2017).…”
Section: Resultssupporting
confidence: 87%
“…1). Our findings correspond to that of Tadesse et al (1997), Hossain et al (2003), Oliveira et al (2012), El-Refaey et al (2013), Morsy et al (2015) and Ilker et al (2018), who reported that some cultivars had high yields under favourable environments, while others adapted to poor environments. In addition, the current results are supported the conclusion of Yothasiri and Somwang (2000), Primomo et al (2002) and Olievira et al (2012) who reported that genotypes with higher stability or good adaptability in a wide range of environment were found for seed yield.…”
Section: Parametric Stability Componentssupporting
confidence: 92%
“…The stability of seed yield in different crops has been statistically evaluated through analysis of GEI interaction in cultivar-adaptation trials conducted over several environments (Crossa, 1990;Piepho, 1998). Results of many previous researches revealed the importance of the genotype by environment interaction in the stability analysis of soybean (Radi et al, 1993;Ablett et al, 1994;Al-Assily et al, 2002;Meotti et al, 2012;Oliveira et al, 2012;Ikeogu and Nwofia, 2013;Silveira et al, 2016;Ilker et al, 2018a, Ilker et al, 2018b.…”
Section: Introductionmentioning
confidence: 99%